STUDENTS EMPOWERMENT THROUGH FIRST AID TRAINING TO ENHANCE EMERGENCY READINESS - Mulyana, Budi; Angin, Mayliana Perangin; Rahman, Fauzan Habibi; Damanik, Vevi Sustria; Susanti, Ayu Retno; Kamelia, Kamelia; Rahmawati, Ratu Dini; Anggraeni, Puspita Dwi; Aulia Hasna, Sifa Faddilah (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2025)
First aid training equips students with the knowledge and confidence to respond effectively to potentially life-saving emergencies. A patient's outcome is significantly influenced by the actions taken at each stage of the integrated emergency management system, including the first aid provided by students before professional health workers arrive. This community service initiative, made possible through the support and collaboration of our partners, is designed to enhance female students' knowledge, skills, response time, and emergency preparedness. The program involved two days of training for 44 female students at Plus Khodizah Islamic High School, using a video-based approach, problem-based learning, and demonstrations of four key skills: basic life support, choking relief, wound and bleeding management, and evacuation techniques. The results showed a significant improvement in students' knowledge, practical skills, and response time, making them more efficient and effective in emergency situations. To support long-term learning, students were provided with instructional videos, pocketbooks, and essential emergency response skills for daily use. This community service has been well-received, with our partners giving an average satisfaction score of 8 out of 10. Overall, the first aid training program has successfully increased students’ emergency readiness by enhancing their knowledge, skills, and responsiveness. Pelatihan pertolongan pertama membekali siswi dengan pengetahuan dan kepercayaan diri untuk merespon secara efisien pada kondisi gawat atau darurat yang berpotensi menyelamatkan nyawa. Keberhasilan pasien tertolong bergantung pada keberhasilan pada setiap tahapan Sistem Penanggulangan Gawat Darurat Terpadu termasuk bagaimana siswi memberikan pertolongan pertama sebelum petugas kesehatan terampil datang. Pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan, keterampilan, respon time dan kesiapan siswi dalam menghadapi kondisi gawat darurat sehari-hari. Metode yang digunakan adalah pelatihan dengan pendekatan video, problem-based learning dan demonstrasi empat keterampilan kepada 44 siswi SMA Plus Khodizah Islamic School selama 2 hari. Keterampilan yang diberikan yaitu bantuan hidup dasar, pertolongan tersedak, pertolongan luka dan perdarahan, dan proses evakuasi. Hasil pengabdian masyarakat ini didapatkan bahwa pengetahuan keterampilan dan respon time siswi meningkat signifikan. Untuk pengetahuan dan keterampilan jangka panjang, siswi dibekali video keterampilan dan buku saku penangan kegawatdaruratan sehari-hari. Pelaksanaan pengabdian masyarakat ini memberikan kepuasan kepada mitra, dimana mitra memberikan skor rata-rata 8 (0-10). Pelatihan pertolongan pertama ini efektif dalam meningkatkan kesiapan melalui peningkatan pengetahuan, keterampilan, dan respon time.